IEEE Conference Record - Abstracts. 2005 IEEE International Conference on Plasma Science 2005
DOI: 10.1109/plasma.2005.359185
|View full text |Cite
|
Sign up to set email alerts
|

Electron Cross-Field Transport in a Miniaturized Cylindrical Hall Thruster

Abstract: Conventional annular Hall thrusters become inefficient when scaled to low power. Cylindrical Hall thrusters, which have lower surface-to-volume ratio, are more promising for scaling down. They presently exhibit performance comparable with conventional annular Hall thrusters. The present paper gives a review of the experimental and numerical investigations of electron crossfield transport in the 2.6 cm miniaturized cylindrical Hall thruster (100 W power level). We show that, in order to explain the discharge cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…1,4 For the miniaturized 100-200 W-class CHTs, the optimal magnetic field configuration was shown to be an enhanced mirror-type (the so-called direct configuration). 6 The highest thruster performance parameters were achieved when the maximum magnetic field at the mirror was ~ 1-1.5 kGauss. 7 In these regimes, the electromagnet coils consumed 50-100 W. For the low power thruster, this additional power consumption reduces drastically the overall thruster efficiency.…”
mentioning
confidence: 99%
“…1,4 For the miniaturized 100-200 W-class CHTs, the optimal magnetic field configuration was shown to be an enhanced mirror-type (the so-called direct configuration). 6 The highest thruster performance parameters were achieved when the maximum magnetic field at the mirror was ~ 1-1.5 kGauss. 7 In these regimes, the electromagnet coils consumed 50-100 W. For the low power thruster, this additional power consumption reduces drastically the overall thruster efficiency.…”
mentioning
confidence: 99%
“…15 Comprehensive studies of the CHT with cusp-type and mirror-type magnetic field configurations are reported elsewhere. 12,15,16 For the miniaturized low power CHT, the optimal magnetic field configuration was shown to be an enhanced mirror-t 17 ype.…”
Section: Miniaturized Cylindrical and Annular Hall Thrustersmentioning
confidence: 99%
“…However, evidence suggests that electronwall collisions and secondary electron emissions (SEEs) are not sufficient to explain the observed cross-field electron transport. [25][26][27][28][29][30] Anomalous electron transport may be due to the presence of short-wavelength instabilities in the azimuthal direction, as highlighted by both experimental and numerical studies. [31][32][33][34] Indeed, the large electron drift velocity in the azimuthal direction acts as a driving force for these instabilities [35][36][37] , which result in large amplitude fluctuations in both the plasma density and the azimuthal electric field.…”
Section: Introductionmentioning
confidence: 99%